'opened out […] like an oyster shell': the Roach bed Portland stone cladding of the Smithsons' Economist Building. Issue 2 (June 2020) - Wigzell, Freya
Abstract : Alison & Peter Smithson's Economist Building in London (1960–1964) has been much written about, but one of its most distinctive features – the Roach bed Portland stone cladding – has been relatively little discussed. Although there have been various retrospective explanations for the choice of this previously unused stone, whose surface is marked by cavities of now vanished shells, no direct evidence from the time fully accounts for the decision. Reliance upon inference, and upon retrospective statements, mean that no definitive explanation for the choice is now possible. Some new evidence from archives and interviews, and a re-examination of the contemporary concerns of the Smithsons, and of their artist friends Eduardo Paolozzi and Nigel Henderson, fellow members of the Independent Group during the 1950s, however, suggest a plausible, though speculative, interpretation. When considered in light of the Smithsons' and their friends' interests in pattern, in hidden orders, and in the problems of 'human association', the choice of Roach bed Portland stone seems less surprising. More than just 'pretty', as Peter Smithson was later to describe the material, it can be seen to connect with a fascination with underlying, non-human, systems of order, while at the same time providing a particularly expressive form of protection for human identity in the modern city.